Hydrogen Absorbing Material in Carbonaceous-Metal Hydride - Mulana, Farid (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2006)
One of the most promising materials for storing hydrogen in solid state would be included in metal-carbon composites. In order to obtain nanocrystalline metal particles encapsulated by crystalline or amorphous carbon, mechanosynthesis of zirconium-carbonaceous composites and alkali metal-carbonaceous composites was performed. For zirconium-carbonaceous composites, only zirconium-carbon black composite absorbed more hydrogen than expected for a mere mixture with the same composition. The higher hydrogen capacity on the zirconium-carbon black composite would be due to some specific sites on the carbonaceous material created during the milling. Another effect of the composite formation was stabilization of zirconium, that is, the composites did not ignite in air. On alkali metal-carbonaceous composites, carbon black has superior effect in composite formation compared with graphite in which some cooperative effect was only detected on alkali metal-carbon black composite. The effect of the carbonaceous composite formation was resistance to air and anti-sticking characteristics to balls and the wall of the vial during the ball milling.